Hyatt Regency Walkway Collapse - Anonymous (Online Ethics Center, 2021)
A summary of the Hyatt Walkway collapse that includes discussion questions.
Case Study / Scenario
Keywords: Catastrophes; Hazards; Disasters; Safety; Engineer/Client Relationships